Clinical practice visits: a rapid review. Issue 9 (7th March 2019) - Forel, Deanne; Marlow, Nicholas; Vandepeer, Meegan; Hill, Andrew G.
Abstract : Background: Practice visits are a peer review activity where one or more healthcare providers visit the practice of another in the same field. The purpose of this exercise is for visitors to observe and review a host's practice in a non‐punitive manner and provide them with constructive feedback as required; ultimately to improve practice quality and patient care. Methods: A rapid review of three biomedical databases was conducted to identify relevant literature published up until 9 April 2018. There were no limits placed on publication date or publication type. Two authors were responsible for study selection and data extraction using a priori inclusion criteria and extraction templates. Study details and key findings were reported narratively and in tables. Results: A total of nine publications, reporting outcomes for eight study groups, were identified as eligible for inclusion in this rapid review. Of these eight, six were observational studies, one was a longitudinal study and one was a randomized controlled trial. Practice visits were considered useful in identifying areas of improvement in professional practice; however, the rate at which these improvements were elicited varied greatly between the included studies. Overall, both hosts and visitors gained insight from the practice visit process and in general their experiences were positive. Conclusions: Based on the evidence provided by the included studies, recommendations for an effective practice visit can be made. Importantly, the poor quality and age of the literature from which these recommendations are based should be considered. Abstract : Practice visits are a peer review activity where one or more healthcare providers visit the practice of another from the same field to provide constructive feedback. This rapid review aimed to determine the effectiveness of practice visits at improving practice quality and patient care.